Peran Konseling Kelompok Pictorial Narrative dalam Meningkatkan Adaptabilitas Karir Pada Mahasiswa Magang PT Swabina Gatra - Regita Nayla Endriani; Idha Rahayuningsih (CV. ITTC INDONESIA, 2025)
This study aims to determine the effectiveness of the role of Life Design Pictorial Narrative group counseling in improving career adaptability among four internship students at PT Swabina Gatra. This research employed a quasi-experimental design using a one-group pretest–posttest model. The participants were four internship students with low to moderate levels of career adaptability based on the Career Adapt-Abilities Scale (CAAS). The intervention was conducted through three stages: Problem Picture, Preferred Outcome Picture, and Baby Steps Picture. Data were collected through CAAS measurements, observations, interviews, and participants’ visual reflections. The results indicate an improvement in career adaptability after the intervention, particularly in the dimensions of career concern, career control, career curiosity, and career confidence. The findings also show that career adaptability is influenced by internal and external supporting and inhibiting factors, such as motivation, intention, curiosity, workload, social support, and workplace communication. Overall, Life Design Pictorial Narrative group counseling is effective in enhancing internship students’ career readiness in a professional work environment.